Pengaruh Karateristik Perusahaan Terhadap Pengungkapan Corporate Social Responsibility - Nur Alif Tomy Pranoto; Kartika Hendra Titisari; Suhendro Suhendro (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Corporate Social Responsibility (CSR) is the social responsibility of a company towards society. In CSR practice, CSR has become an integral part in setting business goals and establishing company policies. Research testing and analysis of the influence of company age, company size, profitability and liquidity on Corporate Social Responsibility (CSR) disclosure. This research uses a purposive sampling method. The sample size is 125 samples or 25 financial sector companies that focus on banking which are listed on the Indonesia Stock Exchange for the 2018-2022 period. The data used is secondary data in the form of financial and sustainable reports with an analysis model, namely multiple regression analysis using SPSS version 25 software. The research results show that company age, company size and liquidity have a significant effect on Corporate Social Responsibility (CSR) disclosure. Meanwhile, profitability has no effect on disclosure of Corporate Social Responsibility (CSR). Keywords: CSR, company age, company size, profitability, liquidity